2014
DOI: 10.1371/journal.pone.0113869
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hydrogen Sulfide from Cysteine in Saccharomyces cerevisiae BY4742: Genome Wide Screen Reveals a Central Role of the Vacuole

Abstract: Discoveries on the toxic effects of cysteine accumulation and, particularly, recent findings on the many physiological roles of one of the products of cysteine catabolism, hydrogen sulfide (H2S), are highlighting the importance of this amino acid and sulfur metabolism in a range of cellular activities. It is also highlighting how little we know about this critical part of cellular metabolism. In the work described here, a genome-wide screen using a deletion collection of Saccharomyces cerevisiae revealed a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…This finding implies an interaction between soluble toxic Sod1 isoforms and the vacuolar H + /ATPase, the protein complex responsible for the acidification process. In line with this, we also observed a significant decrease in the production of H 2 S, a phenotype that has been strongly linked to vacuolar ATPase function (Winter et al, 2014). Further evidence that vacuolar dysfunction occurs as a result of the expression of mutant Sod1 was provided by the observation that these cells also displayed a defect in the process of autophagy, as observed in mouse models of ALS (Mis et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding implies an interaction between soluble toxic Sod1 isoforms and the vacuolar H + /ATPase, the protein complex responsible for the acidification process. In line with this, we also observed a significant decrease in the production of H 2 S, a phenotype that has been strongly linked to vacuolar ATPase function (Winter et al, 2014). Further evidence that vacuolar dysfunction occurs as a result of the expression of mutant Sod1 was provided by the observation that these cells also displayed a defect in the process of autophagy, as observed in mouse models of ALS (Mis et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…A small increase in the number of cells exhibiting multiple vacuoles was also observed for cells lacking SOD1 and for cells expressing mutant Sod1 isoforms (data not shown). Cells with defective vacuolar ATPase function, which is responsible for acidification of the vacuole, have recently been shown to exhibit decreased H 2 S production (Winter et al, 2014). A clear decrease in H 2 S production was observed in Δ sod1 strains expressing mutant isoforms of Sod1 compared with controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cordente et al (2013) used this approach to screen many hundreds of variants of a commercial wine yeast strain for acetic acid production in different grape musts in anaerobic conditions. In Winter et al (2014), a genome-wide screen of the formation of H2S from cysteine of a haploid S. cerevisiae deletion library was undertaken, and the results were validated in standard conditions. Selection, in which strains with the desired phenotype have a selective advantage over the parent strain, is therefore the most efficient means of isolating new strains from mutagenised populations.…”
Section: Wine Yeast Strain Improvement Through Mutagenesis and Selectionmentioning
confidence: 99%
“…The metabolic reactions were compartmentalised between the cytosol and the mitochondria, and transport steps between the compartments and the environment were included. In the context of wine yeast strain development, Winter et al (2014) reported a genome-wide screen of a deletion collection of S. cerevisiae which revealed genes associated with cysteine catabolism and hydrogen sulfide formation. This model significantly enhances the available tools for the systematic functional analysis of the yeast genome (Oliver et al 1998) and is a further step towards replacing trial-and-error based reductionist approaches through a holistic and unbiased selection of targets for yeast strain selection and improvement (Van der Werf et al 2005).…”
Section: Applications Of Microbial Metabolomics In Yeast Research Andmentioning
confidence: 99%
“…Comparative analysis of intracellular metabolites has been instrumental in revealing the function of silent genes, and of genes with hitherto unknown functions (Raamsdonk et al 2001). In the context of wine yeast strain development, Winter et al (2014) reported a genome-wide screen of a deletion collection of S. cerevisiae which revealed genes associated with cysteine catabolism and hydrogen sulfide formation. Adaptive evolution experiments, together with interspecies hybridisation and mutagenesis, represent a strategy that can be used to develop non-genetically modified wine yeast strains (McBryde et al 2006).…”
Section: Applications Of Microbial Metabolomics In Yeast Research Andmentioning
confidence: 99%